Voltage-activated currents in guinea pig pancreatic alpha 2 cells. Evidence for Ca2+-dependent action potentials. - Rorsman, P; Hellman, B (1988)
Glucagon-secreting alpha 2 cells were isolated from guinea pig pancreatic islets and used for electrophysiological studies of voltage-activated ionic conductances using the patch-clamp technique. The alpha 2 cells differed from beta cells in producing action potentials in the absence of glucose. The frequency of these potentials increased after addition of 10 mM arginine but remained unaffected in the presence of 5-20 mM glucose. When studying the conductances underlying the action potentials, we identified a delayed rectifying K+ current, an Na+ current, and a Ca2+ current. The K+ current activated above -20 mV and then increased with the applied voltage. The Na+ current developed at potentials above -50 mV and reached a maximal peak amplitude of 550 pA during depolarizing pulses to -15 mV. The Na+ current inactivated rapidly (tau h approximately 0.7 ms at 0 mV). Half-maximal steady state inactivation was attained at -58 mV, and currents could no longer be elicited after conditioning pulses to potentials above -40 mV. The Ca2+ current first became detectable at -50 mV and reached a maximal amplitude of 90 pA (in extracellular [Ca2+] = 2.6 mM) at about -10 mV. Unlike the Na+ current, it inactivated little or not at all. Membrane potential measurements demonstrated that both the Ca2+ and Na+ currents contribute to the generation of the action potential. Whereas there was an absolute requirement of extracellular Ca2+ for action potentials to be elicited at all, suppression of the much larger Na+ current only reduced the upstroke velocity of the spikes. It is suggested that this behavior reflects the participation of a low-threshold Ca2+ conductance in the pacemaking of alpha 2 cells.